2020
DOI: 10.3390/cancers12071870
|View full text |Cite
|
Sign up to set email alerts
|

SNAIL Promotes Metastatic Behavior of Rhabdomyosarcoma by Increasing EZRIN and AKT Expression and Regulating MicroRNA Networks

Abstract: Rhabdomyosarcoma (RMS) is a predominant soft tissue tumor in children and adolescents. For high-grade RMS with metastatic involvement, the 3-year overall survival rate is only 25 to 30%. Thus, understanding the regulatory mechanisms involved in promoting the metastasis of RMS is important. Here, we demonstrate for the first time that the SNAIL transcription factor regulates the metastatic behavior of RMS both in vitro and in vivo. SNAIL upregulates the protein expression of EZRIN and AKT, known to promote meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…In addition, ITGA2-induced chemoresistance is reversed by upregulation of miR-135b-5p, which inhibits MAPK/ERK and EMT pathways in gastric cancer cells [27]. The expression of ITGA2 is inhibited by silencing SNAIL in rhabdomyosarcoma RH30 cells and the overall metastatic behavior is reduced [28]. However, the role of exosomes-mediated transfer of integrins from CRPC to AR-dependent cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ITGA2-induced chemoresistance is reversed by upregulation of miR-135b-5p, which inhibits MAPK/ERK and EMT pathways in gastric cancer cells [27]. The expression of ITGA2 is inhibited by silencing SNAIL in rhabdomyosarcoma RH30 cells and the overall metastatic behavior is reduced [28]. However, the role of exosomes-mediated transfer of integrins from CRPC to AR-dependent cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 10 Furthermore, SNAIL regulates RMS metastasis by affecting the EZRIN cytoskeletal protein and AKT serine/threonine kinase levels. 11 In addition to the regulation of protein expression, SNAIL is also a crucial regulator of noncoding RNAs, including microRNAs (miRNAs). 7 , 11 SNAIL may affect miRNA expression either indirectly or directly by binding to their promoters or regulatory elements.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In addition to the regulation of protein expression, SNAIL is also a crucial regulator of noncoding RNAs, including microRNAs (miRNAs). 7 , 11 SNAIL may affect miRNA expression either indirectly or directly by binding to their promoters or regulatory elements. 7 In our previous studies, we demonstrated that in RMS cells SNAIL is the regulator of the whole miRNA transcriptome, and gene ontology analysis revealed that the SNAIL-miRNA axis regulates processes associated with differentiation, migration, and reorganization of the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations